Boundary layer flow of dusty fluid on a stretching sheet of another quiescent fluid - Mohd Isa, Sharena; Mohammad, Nurul Farahain (IOP Publishing, 2017)
A research study on boundary layer flow of a dusty viscous fluid past a stretching sheet of another dusty viscous quiescent fluid is conducted. The upper lighter fluid imposes downward on a lower heavier fluid. The existence of solid particles in a dusty fluid either naturally or deliberately in the form of dust, ash or soot suspended in the fluid may influence both upper and lower fluid flow characteristic. Therefore, this study investigates the effects of specific physical parameters such as fluid particle interaction, stretching rate, suction and injection. The governing partial differential equations are transformed into ordinary differential equations by using similarity transformation. The resulting differential equations are solved numerically by using Finite Difference Method with Richardson Extrapolation. The behaviors of physical parameters on velocity profile as well as skin frictions are presented graphically.